α-glucosidase inhibitors for diabetes/blood sugar regulation - Bhatnagar A.; Mishra A. (My University, 2025)
According to a recent analysis, nearly 450 million people get affected by type 2 diabetes, which corresponds to 6.28% of our population. Type 2 diabetes has become one of the ten leading causes of death worldwide. This disease reports over 10 lakh deaths per year, with a current widespread reporting rate of 6000 cases per 100,000; the rate is reckoned to increase to 7100 patients per 100,000 by the end of 2030 (Yang et al. 2018). Diabetes mellitus requires immediate attention because of its increasing burden globally, especially in developed nations, such as America and Europe. Alpha-glucosidase inhibitors are a class of oral medication used in treating type 2 diabetes mellitus. They can be administered alone or in combination therapy with other antidiabetic medications. They are used for patients with low blood sugar tolerance and delayed type 2 diabetes. They are convenient for patients at risk of hypoglycemia or lactic acidosis. Thus, they are not suitable candidates which are on other antidiabetic drugs such as sulfonylureas and biguanides. Alpha-glucosidase inhibitors can also be referred to as starch blockers that help to reduce postprandial blood sugar levels. These enzyme inhibitors do not directly affect insulin secretion or sensitivity, unlike other antidiabetic drugs. Instead, they work by delaying the digestion of sugars found in starchy foods by raising post-meal levels of GLP-1 and lowering HbA1c levels. Alpha-glucosidase inhibitors like acarbose and migitol have shown an increase in expectancy of life in patients with type 2 diabetes mellitus and have proven reduced risk of cardiovascular incidents in patients with reduced glucose tolerance. It has also proven to be effective in stabilizing carotid plaques, lowering hyperglycemia, and can very well counter oxidative stress and endothelial dysfunction. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022. All rights reserved.